Use of Bacillus firmus E65-Talc Based Formulation for The Management of Bacterial Leaf Blight Disease - yadi - suryadi; Dwi Ningsih susilowati; I Made - Samudra (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2021)
It has long been known that bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo), is major bacterial diseases which occured widespread in rice growing countries. This study was performed to determine effect of biological control using endophyte bacteria formulated in talc-based powder against Xoo in rice agroecosystem which grown under organic system of rice intensification (SRI) in Cianjur-West Java. Carriers formulation of talc-based powder was prepared to contain endophytic bacteria of Bacillus firmus (isolate E65) which was previously isolated from the rice field. BLB disease suppression was ranged 2.14% to 97.15%. among cultivars tested, with the average BLB severity among six cultivars was 9.79%. The cv. Inpari 10 (Moderate) showed the lowest disease severity compared with that of resistance cv. Sintanur, Mekongga and Code. This suggests that the biocontrol efficacy of formulation B. firmus E65-talc-based powder was not affected by cultivar susceptibility. The antagonistic bacteria formulation yields up to 9%. The highest yields for each respective treatment treated with talc based-bacterial formulation were obtained using cv. Inpari 10 and Cisantana. The scale-up of biocontrol products that prolongs biocontrol activity may challenged with shelf life of formulation. This study showed advantages of single cultures of bacterial antagonist used in a talc-based formulation is possible to suppress BLB disease and promotes rice yield under SRI field condition.